Triclinic and monoclinic polymorphs of meso‐(E, E)‐1, 1′‐[1, 2‐bis(4‐chlorophenyl)ethane‐1, 2‐diyl]bis(phenyldiazene): the high‐yield synthesis of an unexpected product, concomitant polymorphism and configurational disorder. Issue 1 (1st January 2016) - Mohamed, Shaaban K.; Younes, Sabry H. H.; Abdel‐Raheem, Eman M. M.; Horton, Peter N.; Akkurt, Mehmet; Glidewell, Christopher
Abstract : Pyrazolidine‐3, 5‐diones and their derivatives exhibit a wide range of biological activities. Seeking to explore the effect of combining a hydrocarbyl ring substituent, as present in sulfinpyrazone (used to treat gout), with a chlorinated aryl ring, as present in muzolimine (a diuretic), we explored the reaction between 1‐phenylpyrazolidine‐3, 5‐dione and 4‐chlorobenzaldehyde under mildly basic conditions in the expectation of producing the simple condensation product 4‐(4‐chlorobenzylidene)‐1‐phenylpyrazolidine‐3, 5‐dione. However, the reaction product proved to be meso ‐( E, E )‐1, 1′‐[1, 2‐bis(4‐chlorophenyl)ethane‐1, 2‐diyl]bis(phenyldiazene), C26 H20 Cl2 N4, and a tentative mechanism is proposed. Crystallization from ethanol produces two concomitant polymorphs, i.e. a triclinic form, (I), in the space group P, and a monoclinic form, (II), in the space group C 2/ c . In both polymorphs, the molecules lie across centres of inversion, but in (II), the molecules are subject to whole‐molecule disorder equivalent to configurational disorder with occupancies of 0.6021 (19) and 0.3979 (19). There are no hydrogen bonds in the crystal structure of polymorph (I), but the molecules of polymorph (II) are linked by C—H...π(arene) hydrogen bonds into complex chains, which are further linked into sheets by C—H...N interactions.